Experimental in vivo model to evaluate the impact of Cernitin™ on pain response on induced chronic bladder inflammation. (4th July 2022) - Augé, Céline; Dizeyi, Nishtman; Ramnemark, Lena; Lluel, Philippe; Grabe, Magnus
Abstract: Objective: Inflammation of the urinary bladder may cause burdensome pain also called bladder pain syndrome (BPS). A limitation in understanding BPS pathophysiology is the lack of appropriate preclinical model. Previously published clinical and preclinical studies revealed positive impact of Cernitin™ on pain relief in chronic prostatitis. The objective of this study was to evaluate the effects of Cernitin™ on induced inflammation of the urinary bladder in rats. We also sought to identify biomarkers which might play a role in the management of BPS. Materials and methods: Cystitis was induced by injection of cyclophosphamide (CYP) in female rats. Thereafter, animals were randomly divided into four treatment groups and two control groups. Evaluation of pain scores was assessed by von Frey assay. Expression of pain- and pro-inflammatory biomarkers was determined by enzyme-linked immunosorbent assay (ELISA) and immunohistochemistry. Results: Treatments with Cernitin™ displayed significant anti-nociceptive effects on CYP-induced visceral pain ( p  < .01). In contrast, vehicle-treated animals showed high pain score even at the lowest force. Furthermore, results of ELISA showed that Cernitin™-treated animals had significantly reduced levels of COX-2 (T60, p  < .01; GBX, p  < .05) in bladder tissue homogenate. Immunohistochemical (IHC) staining of bladder tissues showed that Cernitin™-treated animals exhibited less CD45-positive cells, while massive CD45-positive cells infiltration was detected in vehicle-treated animals. IHC also revealed lower SP and PGD2 expression levels in Cernitin™-treated tissues. Conclusions: Cernitin™ components reduced pain score and inflammatory marker COX-2. Our findings suggest a potential therapeutic role for Cernitin™ in the management of BPS.